Chemokines in allergic conjunctivitis. Issue 5 (October 2020) - Erdinest, Nir; London, Naomi; Solomon, Abraham
Abstract : Purpose of review: Chemokines are a large group of low molecular weight cytokines that attract and activate leukocytes throughout the body and therefore have a key role in the framework of late-phase allergic responses. The purpose of this article is to provide an overview of the main chemokines involved in allergic conjunctivitis, their primary functions and their physiological roles, and therapies targeted at chemokines and their receptors for ocular allergic diseases. Recent findings: In recent years, there have been considerable advances in the understanding of ocular pathophysiology of ocular surface inflammatory diseases including both allergic eye diseases and dry eye syndrome. Several therapies being developed for dry eye inflammation are recognized as possible therapies for ocular allergic diseases as there are often common chemokines involved in both disease spectra. Summary: Chemokines represent an integral part of the late-phase cascade of ocular allergic inflammation. A deep understanding of specific chemokines and their interactions will help in targeting therapies to effectively manage ocular clinical findings and symptoms of allergic eye disease.